Odpowiedzi

2009-10-05T19:04:51+02:00
A) -2/3x = -2
2x = 6
x = 3

b) -14x - 7 = 4
-14x = 11
x = -11/14

c) 0,5x +1 + 3 = 0,5
0,5x = -3,5
x =-7

d)
-3/4x - 0,25 = 0,25
-3/4x = 0,5
-3x = -1
3x = 1
x = 1/3
2009-10-05T19:08:51+02:00
A)1/3x-x=-2
1/3x-3/3x=-2
-2/3x=-2 ÷(-2/3)
x=-2*(-3/2)
x=6/2=3
b)-14x-7=4
-14x=4+7
-14x=11
x=-11/14
c)-x/2+x=1/2-2/2-3
-x/2+x=1/2-2/2-6/2
-x/2+x=-7/2
-x/2+2x/2=-7/2
x/2=-7/2
x=-7/2*2
x=-14/2=-7
d)1/4x=1/4+1/4
1/4x-4/4x=2/4
-3/4x=2/4
x=2/4*(-4/3)
x=-8/12=-4/6=-2/3
2009-10-05T19:13:21+02:00
A)⅓x-x=-2
⅓x-3/3x=-2
-⅔x=-2 | :(-⅔)
x=-2*(-3/2)
x=6/2
x=3

b)-7(2x+1)=4
-14x-7=4
-14x=4+7
-14x=11 |:(-14)
x=-11/14

c)3-x/2 + x+2/2=1/2 |*2
6-x+2x+2=1
x=1-2-6
x=-7
lub <w zależności co jest nad kreską ułamkową>
3-x/2 + x+2/2=1/2 |*2
3-x+x+2=1
-x+x=1-2-3
0=-6
równanie sprzeczne

d)1/4x-x-1/4=1/4
-¾x=¼+¼
-¾x=½ | * (-4/3)
x=-⅔